Adolescents’ Self-Concept and their Attitudes towards Parents Teachers, and Police Authority - Huma Zafar, Tanzila Nabeel, Muhammad Tahir Khalily (Pakistan Journal of Psychology, 2013)
The aim of the study was to empirically examine the relationship between adolescents’ self-concept and their attitude towards authority figures. The sample comprised of 600 adolescents between the ages of 12 to 19 years. In order to fulfill the objectives of the study, a short demographic sheet that comprised of participants’ personal information; four attitudinal scales and an Urdu adjective list (UACL) to measure adolescents’ self concept were used. The study consisted of two parts. Part I dealt with developing the attitude scales, determining their psychometric properties and pilot study and Part II consisted of the main study. The results of our main study revealed that adolescents between the ages of 12-19 years reported positive self-concept and attitude towards parents and teachers while, reported negative attitude towards police authority. It was also found that there were some differences in the adolescents' self-concept and their attitude towards authority with respect to age, gender and socio-economic status.